THE SALUD Y SEGURIDAD OCUPACIONAL EN LA GESTIÓN DE DOCUMENTOS COMERCIALES - Reis, João Victor dos; Rodolpho, Daniela (Revista Interface Tecnológica, 2020)
Nowadays, everything that is generated has its registration, when people are born, the registration of their birth happens, when a company is born it also needs to be registered, just as a piece is produced it will also have its registration in some way. All of these are documents, files, information of extreme importance. Large amounts of information are produced in companies, from their documents to their routine activities. Unfortunately, the form of storage is not always organized and does not receive proper care. The management of a company’s document collection can also harm the health of the professional who needs to handle the documents on a daily basis in order to meet the information needs requested by the company that produced it, or of users who seek the information. Document outsourcing takes care of and deals with specialized procedures, organizes and manages appropriately and effectively for the maintenance of documents. And with all this, the company pays cheaper to keep the document, freeing up a huge space in the stock. And the main thing without putting your workers at risk.